Yield Stability and Adaptability of Aromatic New Plant Type (NPT) Rice Lines - Angelita Puji Lestari; Buang Abdullah; Ahmad Junaedi; Hajrial Aswidinnoor (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2010)
Aromatic new plant type (NPT) rice lines were selected to obtain high yielding and aromatic lines. The objectives of the research were to study the yield stability and adaptability of 35 NPTrice lines across different environment, with Ciherang and Sintanur as check varieties. The lines planted at two locations, Bogor and Pusakanagara in two seasons (2009 dry and wet seasons, DS-WS). The experiment used randomized complete block design (RCBD), with three replications. The 21-day-old seedlings were planted with spacing of 20 cm x 20 cm, with a plot size of 2 m x 5 m. Yield stability and adaptability were estimated by using coeffi cient regression (bi) and general mean of yield by Finlay-Wilkinson method. Combined analysis of variance showed that lines (G), environment (E), and the G x E interaction were signifi cantly different. Lines showed different stability and adaptability . Several lines yielded higher than Ciherang variety . Nine lines were classifi edasstable and widely adapted at the marginal environment, i.e IPB 116-F-3-1, IPB 117-F-4-1, IPB-117-F-14-2, IPB-117-F-15-2, IPB-117-F-17-5, IPB 140-F-1-1, 140-F-IPB, 2-1, IPB 140-F-3, and IPB 149-F-2. Lines IPB 113-F-2, IPB 140-F-4, IPB 140-F-6, IPB 140-F-7, and B11738-MR-Si-1-2-1-2 were not stable and adapted only in optimum environmental condition (bi > 1) while IPB 116-F-46-1, IPB-117-F 17-4, IPB-117-F 18-3 and B11955-MR-84-1-4 has the value of bi < 1 or adaptable to marginal environments.Keywords: aromatic rice, NPT rice, yield stability